Предмет: Алгебра, автор: kosoy

(3/25-a^2+1/a^2-10a+25)*(5-a)^2/a+3a/a+5=

Ответы

Автор ответа: dtnth
0

(frac {3}{25-a^2}+frac {1}{a^2-10a+25})*frac{(5-a)^2}{a}+frac {3a}{a+5}= (frac {3*(5-a)}{(5-a)^2*(a+5)}+frac {1*(a+5)}{(5-a)^2*(a+5)})*frac{(5-a)^2}{a}+frac {3a}{a+5}= (frac {15-3a+a+5)}{(5-a)^2*(a+5)})*frac{(5-a)^2}{a}+frac {3a}{a+5}= (frac {20-2a}{(5-a)^2*(a+5)})*frac{(5-a)^2}{a}+frac {3a}{a+5}= (frac {20-2a}{(a+5)a})+frac {3a}{a+5}=(frac {20-2a+3a^2}{(a+5)a})

Похожие вопросы
Предмет: Математика, автор: abitovamedina8
Предмет: Биология, автор: david435
Предмет: Математика, автор: ник1993